Fair Value Disclosures Beyond SFAS 157 - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2012)
Our study examines the factors that influence the fair value disclosures in the SFAS 157 footnote, and how these disclosures affect investors’ uncertainty regarding these fair value estimates, particularly Level 3 estimates. We find that more Level 3 items, more transfers from Level 1 and Level 2 items to Level 3 items, higher gains from Level 3 items, and the early adoption of SFAS 157 are associated with more fair value disclosures. We also find that the following are associated with more fair value disclosures: banks, more analyst coverage, greater auditor independence, and firms with more business segments. Next, we show that managerial discretion to provide more fair value disclosures reduces the uncertainty associated with Level 3 assets. This effect is stronger when there is a less sophisticated investor base and when there are more concurrent 10-K filers. Overall, our results suggest that fair value disclosures that firms provide beyond SFAS 157’s three-level estimates help investors interpret fair value estimates more precisely.